Discussing the common(s) in Neoliberal Capitalism: From Ontology to Politics - Saidel, Matías Leandro (2018)
This article intends to think the relationship between neoliberal capitalism and thecommon(s). First, it ties to define the common both in ontological and political terms,stressing the similarities and differences between the common, commons and commongoods. Then, it characterizes their relationship with neoliberal capitalism interms of dispossession, expropriation and configuration. Finally, it discusses if thecommon can be thought as an alternative form of cooperation and self-governmentwith regards to neoliberalism and to what extent it can be posed as a complete alternativeto the state.